Evaluasi Website Institut Agama Islam Negeri (IAIN) Jember menggunakan Metode Human Centered Design (HCD) dan System Usability Scale (SUS) - Ifadhatur Rohmah; Satrio Hadi Wijoyo; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
IAIN Jember is one of the universities that own a website, the website is used as a means of disseminating information related to campus profiles, lecture activities, and campus announcements. When using the website, we found several usability problems, one of which was a menu that didn't function or didn't display any action. Based on the conditions that occured, the IAIN Jember website requires evaluating and there are improvements related to the interface involving the three aspects of usability according to (ISO 9241-11 (1998)). Improvements will be made using the Human Centered Design (HCD) method and Usability Testing which consists of effectiveness, efficiency and a System Usability Scale (SUS) questionnaire for satisfaction. Respondents consisted of two groups, namely parties related to IAIN Jember and the general public. As for the effectiveness aspect, an increase in value was obtained by 41.67% for parties related to IAIN Jember and 30% for the general public. In the aspect of efficiency, parties related to IAIN Jember received an increase of 68% while the general public got 58%. Furthermore, the satisfaction aspect using the System Usability Scale (SUS) questionnaire was given to 20 respondents and obtained an increase of 39.85. Therefore, it is evident if the design solution has a better usability value.